GUARANTEEING THE RIGHTS OF INTERNALLY DISPLACED PERSONS IN THE CONTEXT OF ENSURING NATIONAL SECURITY OF UKRAINE (THEORETICAL AND LEGAL ASPECT) (Bulletin of criminological association of Ukraine, 2023)
The article highlights the main areas of activity of the components of the security and defense sector of Ukraine, which correspond to guaranteeing the full implementation of the rights of internally displaced persons, from the standpoint of a general theoretical analysis. On the basis of the analysis of the provisions of the current legislation on national security, five conceptual bases of the activities of national security agencies aimed at ensuring the rights of internally displaced persons have been determined: ensuring the control functions of the Verkhovna Rada of Ukraine over the activities of law enforcement agencies in order to guarantee their unwavering and unconditional compliance with the requirements of the current legislation , the implementation of preventive protective measures to guarantee the exercise of rights by internally displaced persons, the implementation of consultations by the heads of national security bodies with local authorities and local self-governments on the issues of ensuring the rights of internally displaced persons, the establishment of interaction between national security bodies and military administration bodies during planning and implementation special forces, the involvement of authorities in the development of state-targeted strategic documents in the field of national security and defense, taking into account guarantees of the realization of rights and interests provided for by legislation for internally displaced persons.
Keywords: internally displaced persons; rights of internally displaced persons; guarantees; state authorities; national security of Ukraine; territorial integrity